Project Management in China : Softskills as Succes Factors. - Wolff, Christian (Diplomica Verlag, 2008)
HauptbeschreibungThe companies and their business environment are facing drastic challenges within the age of globalisation. On the one hand, the companies are exposed to market saturation and enormous pressure in Europe and the USA, while on the other hand, they notice attractive production locations and a huge market potential in China. In the highly industrialised nations, migration to so-called low cost countries has become a business management trend. When it comes to the construction of new industrial facilities - which is the foundation for producing new products, project management bec.